Hormonal regulation of vascular endothelial growth factor A (VEGFA) gene expression in granulosa and theca cells of cattle. (11th May 2019) - Nichols, Jacqueline A; Perego, Maria Chiara; Schütz, Luis F; Hemple, Amber M; Spicer, Leon J
Abstract: Vascular endothelial growth factor A (VEGFA) stimulates angiogenesis and is associated with increased vascularity in ovarian follicles of cattle. The objectives of this study were to investigate the developmental and hormonal regulation of VEGFA expression in ovarian granulosa and theca cells (TC ) of cattle. Bovine ovaries were collected from a local slaughterhouse and granulosa cells (GC ) and TC were collected from small (SM ; 1 to 5 mm) and large (LG ; 8 to 20 mm) follicles. Cells were collected fresh or cultured in serum-free medium and treated with various factors that regulate angiogenesis and follicular development. RNA was collected for analysis of VEGFA mRNA abundance via quantitative PCR. In SM-follicle GC (SMGC ), prostaglandin E2 (PGE2) and FSH decreased ( P < 0.05) VEGFA mRNA abundance by 30 to 46%, whereas in LG-follicle GC (LGGC ), PGE2 and FSH were without effect ( P > 0.10). In SMGC, dihydrotestosterone (DHT ), sonic hedgehog (SHH ), and growth differentiation factor-9 (GDF9 ) decreased ( P < 0.05) VEGFA expression by 30 to 40%. Fibroblast growth factor-9 (FGF9) and estradiol (E2) were without effect ( P > 0.10) on VEGFA mRNA in both SMGC and LGGC, whereas progesterone increased ( P < 0.05) VEGFA mRNA in LGGC but had no effect in LGTC. Bone morphogenetic protein-4 (BMP4 ), LH, and FGF9 increased ( P < 0.05) abundance of VEGFA mRNA by 1.5- to 1.9-fold in LGTC. Insulin-like growth factor-1 (IGF1) was without effect ( P > 0.10) on VEGFA mRNA in both TC and GC. An E2F transcription factor inhibitor, HLM0064741 (E2Fi), dramatically (i.e., 8- to 13-fold) stimulated ( P < 0.01) the expression of VEGFA mRNA expression in both SMGC and LGTC. Abundance of VEGFA mRNA was greater ( P < 0.05) in LGGC and SMGC than in LGTC. Also, SMTC had greater ( P < 0.05) abundance of VEGFA mRNA than LGTC. In conclusion, VEGFA mRNA abundance was greater in GC than TC, and VEGFA expression decreased in TC during follicle development. Some treatments either suppressed, stimulated, or had no effect on VEGFA expression depending on the cell type. The inhibition of E2F transcription factors had the greatest stimulatory effect of all treatments evaluated, and thus, E2Fs may play an important role in regulating angiogenesis during follicle growth in cattle.